Actes de conférence - Trébuchon, Jean-François (BOIS & FORETS DES TROPIQUES, 2020)
ABRUSCATO S., JOA B., WINKEL G. (EDS.), 2020. GOVERNING AND MANAGING FORESTS FOR MULTIPLE ECOSYSTEM SERVICES ACROSS THE GLOBE. BONN, GERMANY, 26-28 FEBRUARY 2020 – BOOK OF ABSTRACTS. GERMANY, EUROPEAN FOREST INSTITUTE, IUFRO, 119 P. HARUTHAITHANASAN M., PINYOPUSARERK K., NICODEMUS A., BUSH D., THOMSON L. (EDS), 2019. CASUARINAS FOR GREEN ECONOMY AND ENVIRONMENTAL SUSTAINABILITY. KRABI, THAILAND, 21-25 OCTOBER 2019. THAÏLAND, KASETSART UNIVERSITY, IUFRO, 319 P. ALDAZ D., KANT S. (EDS), ET AL., 2019. SUSTAINABILITY: TRANSDISCIPLINARY THEORY, PRACTICE, AND ACTION (STTPA CONFERENCE 2019). TORONTO, USA, 16-18 OCTOBER 2019. UNIVERSITY OF TORONTO MISSISSAUGA, IUFRO, 282 P.